2015
DOI: 10.1590/0103-8478cr20140764
|View full text |Cite
|
Sign up to set email alerts
|

Propagação de Thunbergia mysorensis (Wight) por estaquia

Abstract: RESUMO A estaquia é um método muito eficiente de propagação de plantas. Objetivando avaliar o efeito da época de coleta do material (verão e primavera) e concentrações de ácido indolbutírico (AIB : 0; 1500; 3000; 6000mg L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…No effect of IBA concentrations indicates that the survival of sapucaia hardwood cuttings is not related to the regulator, but actually to the type of cutting used. This indicates an absence of toxicity of the IBA at the concentrations used, since it is easily observed by the marked reduction in rooting or death of cuttings with increasing concentration of idol-3butyric acid, according to Heintze et al (2015). In general, the hardwood cuttings in our study showed a good survival rate, with a mean of 52.75%, during the period evaluated.…”
Section: Rooting Potential Of Sapucaia Cuttingssupporting
confidence: 62%
“…No effect of IBA concentrations indicates that the survival of sapucaia hardwood cuttings is not related to the regulator, but actually to the type of cutting used. This indicates an absence of toxicity of the IBA at the concentrations used, since it is easily observed by the marked reduction in rooting or death of cuttings with increasing concentration of idol-3butyric acid, according to Heintze et al (2015). In general, the hardwood cuttings in our study showed a good survival rate, with a mean of 52.75%, during the period evaluated.…”
Section: Rooting Potential Of Sapucaia Cuttingssupporting
confidence: 62%
“…Para o fator número de folíolos, ocorreu o aumento no percentual de enraizamento em estacas com mais folíolos (66%) como verificado por Vignolo et al (2014) e Heintze et al (2015), e o não enraizamento das estacas sem folíolos. Assim, a presença de folhas nas estacas confirma o papel chave destas para a formação do novo sistema radicular, sendo responsável pela produção de assimilados e de substâncias como auxinas, sendo esta última sintetizada nesses locais (TAIZ e ZEIGER, 2009).…”
Section: Resultsunclassified
“…In contrast, Heintzei et al [22] and Hussein [23] observed in Thunbergia mysorensis and Thunbergia grandiflora higher rooting percentage in cuttings collected in the spring. In Table 2, it was observed that there were no differences in the rooting percentage of stem cuttings treated with IBA and boric acid applied separately, as well as IBA and boric acid applied combined.…”
Section: Sources Of Variationmentioning
confidence: 86%